Persistence and cycles in the US federal funds rate - Guglielmo Maria Caporale; Luis A. Gil-Alana (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper uses long-range dependence techniques to analyse two important features of the US Federal Funds effective rate, namely its persistence and cyclical behaviour. It examines annual, monthly, bi-weekly and weekly data, from 1954 until 2010. Two models are considered. One is based on an I(d) specification with AR(2) disturbances and the other on two fractional differencing structures, one at the zero and the other at a cyclical frequency. Thus, the two approaches differ in the way the cyclical component of the process is modelled. In both cases we obtain evidence of long memory and fractional integration. The in-sample goodness-of-fit analysis supports the second specification in the majority of cases. An out-of-sample forecasting experiment also suggests that the long-memory model with two fractional differencing parameters is the most adequate one, especially over long horizons.
Keywords: C32; E43; 330; Federal Funds rate; persistence; cyclical behaviour; fractional integration; Zins; Hysteresis; Zeitökonomie; Konjunktur; Schätzung; USA